Discovery of a novel tumour metastasis-promoting gene, NVM-1 - Thiele, Wilko; Novac, Natalia; Mink, Sigrun; Schreiber, Caroline; Plaumann, Diana; Fritzmann, Johannes; Cremers, Natascha; Rothley, Melanie; Schwager, Christian; Regiert, Thomas; Huber, Peter E.; Stein, Ulrike; et al. (The journal of pathology, 2011)
We have previously reported that over-expression of a panel of 119 genes correlates with the metastatic potential of pancreatic carcinoma cells. We sought to identify and functionally characterize candidate tumour metastasis promoting genes among this library using a secondary phenotype-assisted screen. Here we report the discovery of the metastasis-promoting function of a hitherto not characterized gene located on chromosome 14 (ORF138), which we have named ‘novel metastasis-promoting gene 1’ (NVM-1). The NVM-1 transcript is extensively alternatively spliced, is expressed endogenously in a number of different tissues, and is strongly over-expressed at the protein level in a variety of human tumour types. Importantly, NVM-1 expression stimulates the migratory and invasive behaviour of tumour cells and promotes metastasis formation in experimental animals in vivo. Up-regulation of FMNL2 and MT1E and down-regulation of TIMP4 and MHC-I is observed as a consequence of NVM-1 expression. Together these data identify NVM-1 as a gene that is functionally involved in tumour metastasis, and suggest that NVM-1 may constitute a promising therapeutic target for inhibition of tumour metastasis. Copyright © 2011 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Gesehen am 02.11.2022